Taurocholic acid induces intrahepatic cholangiocyte cell proliferation via activating NRAS and YAP1 - Lum Fube; Arul Thason; Elizabeth Taliaferro; Carol Heckman; Surya Amarachintha (PLoS ONE, 2026)
Biliary atresia is a neonatal cholangiopathy characterized by loss of the extrahepatic bile duct causing bile acid accumulation in the liver and subsequent fibro inflammation and abnormal proliferation of intrahepatic ducts. Further, BA liver develops fibrosis, progresses to cirrhosis, and ultimately results in liver failure requiring liver transplantation. NRAS, an oncoprotein, acts as an effector in cholangiocyte cell proliferation and differentiation. We hypothesize that elevated levels of Taurocholic acid (TCA), a conjugated bile acid, activates YAP1 via NRAS, inducing cholangiocyte proliferation. Our experiments using mouse intrahepatic cholangiocyte cells treated with TCA showed significant proliferation of cells at 100 μM compared to control, 10, and 1000 µM. Immunofluorescence staining with KRT19 and EPCAM antibodies showed neither loss of protein expressions nor altered morphology of cholangiocyte cells with TCA treatments suggesting no loss of cholangiocyte integrity. Fluorescent images measured by Image-J showed elevated NRAS and YAP1 expressions in cells treated with 100 µM TCA for two days compared to control. Further, colocalization analysis revealed YAP1 was translocation to the nucleus presumably. There it can act as a transcription factor and induce TEAD1 expression. In addition, NRAS overexpressed at 100 μM of TCA activated downstream targets MAPK1 . We conclude that TCA induces abnormal cholangiocyte cell proliferation by triggering NRAS production and causing a downstream activation and translocation of YAP1. However, TCA at lower doses showed no significant impact on cholangiocyte cells but at higher doses caused toxicity and cell death.